Ag nanoshell catalyzed dedying of industrial effluents. Issue 38 (29th March 2016) - Vellaichamy, Balakumar; Periakaruppan, Prakash
Abstract : A rapid way to dedye industrial effluents is reported herein using silver nanoshells (Ag-NSs) as a green catalyst. Abstract : A rapid way to dedye industrial effluents is reported herein using silver nanoshells (Ag-NSs) as a green catalyst. Ag-NSs were synthesized using Crataeva religiosa leaf extract as both a reducing and stabilizing agent, and they were characterized by UV-visible spectroscopy, FT-IR spectroscopy, XRD, HR-TEM and EDX analysis. The green synthesized Ag-NSs catalyze in a minute the degradation of organic dye pollutants such as (1) methylene blue, (2) rhodamine-B, (3) safranin, (4) methyl orange, (5) eosin yellow, (6) rose bengal, (7) methyl red, (8) rhodamine-6G, (9) indigo, (10) crystal violet, (11) malachite green and (12) victoria blue from an aqueous environment using NaBH4 . Ag-NSs are able to be conveniently separated from an aqueous environment after catalytic dedying and reusable even after five cycles. The formation of Ag-NSs and dedying mechanism have also been investigated and discussed.